2007
DOI: 10.1590/s0100-204x2007000800015
|View full text |Cite
|
Sign up to set email alerts
|

Controle biológico de nematóides gastrintestinais de caprinos em clima semi-árido pelo fungo Monacrosporium thaumasium

Abstract: O objetivo deste trabalho foi avaliar a viabilidade do fungo nematófago Monacrosporium thaumasium, no controle de larvas infectantes de nematóides gastrintestinais de caprinos em campo, no Semi-Árido cearense. Uma área de 20 ha, com pasto recém-formado, livre de vermes, foi dividida em quatro piquetes de 5 ha. Em cada piquete, foi formado um grupo constituído por nove caprinos, onde cada animal recebeu os seguintes tratamentos, durante os meses de abril a junho de 2002: grupo 1, 10 g de péletes por via oral, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…In an in vivo study where fungi were used in the sheep diet, Alves et al (2003) reported an efficacy of 88.8% in the reduction of FEC in animals treated with 20 g of Monacrosporium thaumasia, twice a week. Weekly doses of 2 to 2.5 g of mycelia from this fungus were effective in reducing the FEC number and resulted in greater BW gain than that in other groups (ARAÚJO et al, 2007). These results indicate that the use of fungi in controlling haemonchosis might be a promising alternative, contributing to a reduction of worming with recourse to synthetic products.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In an in vivo study where fungi were used in the sheep diet, Alves et al (2003) reported an efficacy of 88.8% in the reduction of FEC in animals treated with 20 g of Monacrosporium thaumasia, twice a week. Weekly doses of 2 to 2.5 g of mycelia from this fungus were effective in reducing the FEC number and resulted in greater BW gain than that in other groups (ARAÚJO et al, 2007). These results indicate that the use of fungi in controlling haemonchosis might be a promising alternative, contributing to a reduction of worming with recourse to synthetic products.…”
Section: Discussionmentioning
confidence: 72%
“…Fungi produce anthelmintic substances and represent a promising alternative for the control of GN (ARAÚJO et al, 2007). The fungus Agaricus blazei, commonly known as "mushroom of the sun," contains several compounds with therapeutic and nutritional interest and it has been indicated in the complementary therapy of neoplasias and other alterations (DIAS et al, 2002;NOVAES et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Araújo et al (2004b) reported that treatment with M. thaumasium pellets decreased pasture contamination, reducing animal EPG up to a 100%, rendering the anti-helminth treatments unnecessary. In a recent study, Araújo et al (2007) evaluated the viability of M. thaumasium in pellet form to control larvae infecting goats in the semi-arid region in Ceará. They found EPG reduction in animals treated with pellets once a week, as well as smaller parasitic load and higher weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Nematophagous fungi, especially the genera Duddingtonia, Monacrosporium and Arthrobotrys, have predatory capacity on infective larvae (L 3 ) of gastrointestinal nematode parasites of domestic animals (Araú jo et al, 2004b(Araú jo et al, , 2006Campos et al, 2007). These genera are recognized only as predators, and the predatory capacity of the species D. flagrans and M. thaumasium, M. sinense and A. robusta has been thoroughly discussed and proved in the control of L 3 of gastrointestinal nematode parasites of ruminants, horses and small ruminants (Castro et al, 2003;Chandrawathani et al, 2004;Araú jo et al, 2006Araú jo et al, , 2007Dias et al, 2007). However, the predatory capacity of these species had never been tested on larvae of A. vasorum.…”
Section: Discussionmentioning
confidence: 99%
“…Predatory fungi are certainly the most studied groups and show the greatest potential for biological control (Nordbring-Hertz et al, 2002;Araú jo et al, 2007). The species Duddingtonia flagrans, Monacrosporium thaumasium, M. sinense and Arthrobotrys robusta are identified as nematophagous fungi and have been studied for their potential as biological control agents for gastrointestinal nematodes of domestic animals (Araú jo et al, 2006(Araú jo et al, , 2008Campos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%